Mapping the Folklores of a Disrupted Everyday: Countermapping the Pandemic Life - Concillado, Aljon I. (BANWAAN: The Philippine Journal of Folklore; Vol 2 No 02 (2022): Banwaan: The Philippine Journal of Folklore, 2023)
Taking notes from Denis Wood's A Narrative Atlas of Boylan Heights (2008) and John Eyles' The Geography of Everyday Life (1989), this paper would highlight the "talking maps" of certain parts of Metro Manila, relative to the perspective of the author whose frequent encounters with the mapped places are central. This work shall present my three personal cartographies: (1) Marthopper, showing my routes towards nearby shops during the height of tight restrictions brought by pandemic-related lockdowns, (2) Choking Bottlenecks, a map showing a commuter's perspective of traffic conditions in his primary thoroughfare, Commonwealth Avenue and (3) Hues of Green, a map showing the available greenspaces in Metro Manila concerning limited outdoor activities to such spaces. I intend to highlight the significance of my cartographies in understanding the new everyday life I had to deal with due to the pandemic restrictions. While narrative maps of places with major conflicts and/or other events of global interest may be easy to come by, cartographies that represent the daily life of a middle-class young adult, especially in the context of Philippine urbanity aren't that many. Done in a contemporary, unconventional style, these maps tell the story of my everyday, lived experiences during the pandemic.